2015
DOI: 10.1002/gps.4337
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of self-defined memory problems vary in south Asian minority older people who consult a GP and those who do not: a mixed-method pilot study

Abstract: Differences in perceptions may influence the decision about consulting a GP. Similarly, consultation for memory problems appears linked to extent physical health problems and mental health consultation (depression). These variations reported on a small scale in this pilot study suggest the need to explore the impact of perceptions on rates of GP consultation, so as to improve timely diagnosis and access to appropriate services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Despite living for several decades in the United Kingdom, and also having family members in the area, many older migrants are not claiming welfare benefits they are entitled to or do not know about how to access social care services to support them with the tasks of daily living (See Case Study 1). This trend has also been found in a number of previous studies of migrants in a variety of host countries (Bolzman et al, 2004;Giebel et al, 2016;Ip et al, 2007;Willis et al, 2016).…”
Section: Themes From the Work Of Pukar With Older Migrants Changing Fsupporting
confidence: 81%
See 1 more Smart Citation
“…Despite living for several decades in the United Kingdom, and also having family members in the area, many older migrants are not claiming welfare benefits they are entitled to or do not know about how to access social care services to support them with the tasks of daily living (See Case Study 1). This trend has also been found in a number of previous studies of migrants in a variety of host countries (Bolzman et al, 2004;Giebel et al, 2016;Ip et al, 2007;Willis et al, 2016).…”
Section: Themes From the Work Of Pukar With Older Migrants Changing Fsupporting
confidence: 81%
“…Karl et al (2016) found that older migrants consider returning to their host country at the point of retirement and then again when needing round-the-clock care (Liversage & Mizrahi Mirdal, 2016). Some research has indicated that migrants underuse public care services (Bolzman, Poncioni-Derigo, Vial, & Fibbi, 2004;Giebel et al, 2016) due to a lack of knowledge about what is available (Ip et al, 2007;Willis et al, 2016) as well as stigma around certain conditions, such as dementia and Alzheimer's (Giebel et al, 2016;Li, Hatzidimitriadou, & Psoinos, 2014). However, in a study of older migrants in Switzerland, Bolzman and Vagni (2016) found that migrants were as likely as the host population to use public care services.…”
Section: Older Migrants and Circulations Of Carementioning
confidence: 99%
“…29 Giebel et al looked at the differences in the perceptions of South Asians who do and do not consult a general practitioner (GP) about dementia. 20 They found those who did not consult a GP were significantly more likely to consider memory problems as given by God, with the view that medical intervention was therefore inappropriate. In a case study of a Muslim, Pakistani patient accessing healthcare for dementia in the UK, Regan further highlighted the importance of understanding a person’s religious community and its role in providing both support and reducing stigma and isolation.…”
Section: Resultsmentioning
confidence: 99%
“…Belonging to an ethnic minority group can also be leading to inequalities in diagnosis and care access in dementia [9]. People from black and minority ethnic (BAME) groups are often found to experience delays in receiving a diagnosis, with symptoms also being attributed to faith by some resulting in delays or general noncontact with GPs about their symptoms [10]. In line with other research on various BAME groups, Sagbaken et al [11] reported language barriers and faith-related help-seeking attitudes as major barriers to receiving a dementia diagnosis in ethnic minority migrants in Norway.…”
mentioning
confidence: 99%